Numerous meanings : the meaning of English cardinals and the legacy of Paul Grice - Bultinck, Bert (Current research in the semantics/pragmatics interface, 2005)
Outlandish as it may seem to the uninitiated, the meaning of English cardinal numbers has been the object of many heated and fascinating debates. Notwithstanding the numerous important objections that have been formulated in the last three decades, the (neo- )Gricean, scalar account is still the standard semantic description of numerals. In this book, Bultinck writes the history of this implicature-driven approach and demonstrates that it suffers from methodological insecurity and postulates highly non-conventional meanings of numerals as their "literal meaning", while it confuses the level of.